2015
DOI: 10.1177/0884533615591606
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Severity of Parenteral Nutrition Medication Errors at a Large Children's Hospital After Implementation of Electronic Ordering and Compounding

Abstract: We conclude that PN practices that conferred a meaningful cost reduction and a lower error rate (2.7/1000 PN) than reported in the literature (15.6/1000 PN) were ascribed to the development and implementation of practices that conform to national PN guidelines and recommendations. Electronic ordering and compounding programs eliminated all transcription and related opportunities for errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 20 publications
0
47
1
2
Order By: Relevance
“…Brown et al only defined three prescribing error types (volume error, calcium/phosphate solubility error, osmolarity error) (16). In contrast to our study, MacKay et al assigned compatibility errors to the administration process, not to prescribing (29). …”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Brown et al only defined three prescribing error types (volume error, calcium/phosphate solubility error, osmolarity error) (16). In contrast to our study, MacKay et al assigned compatibility errors to the administration process, not to prescribing (29). …”
Section: Discussioncontrasting
confidence: 99%
“…MacKay et al conducted a similar study in a children’s hospital. Most errors arose during administration (29). Both studies reported a rate of MEs related to the prescription, transcription, preparation and administration of PN of only 6% (28) and 0.27% (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Electronic medication prescribing and atuomated dose checking [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] Computerized physician order entry (n = 5)…”
Section: Intervention Type Example Of Intervention Referencesmentioning
confidence: 99%